2019
DOI: 10.1016/j.redox.2019.101293
|View full text |Cite
|
Sign up to set email alerts
|

OxyR senses sulfane sulfur and activates the genes for its removal in Escherichia coli

Abstract: Sulfane sulfur species including hydrogen polysulfide and organic persulfide are newly recognized normal cellular components, and they participate in signaling and protect cells from oxidative stress. Their production has been extensively studied, but their removal is less characterized. Herein, we showed that sulfane sulfur at high levels was toxic to Escherichia coli under both anaerobic and aerobic conditions. OxyR, a well-known regulator against H2O2, also sensed sulfane sulfur, as revealed via mutational … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 68 publications
1
60
0
Order By: Relevance
“…S5) (35). This suggests either that OxyR does not respond directly to sulfane sulfur in A. baumannii as previously observed in E. coli (44) or that the induction of the OxyR regulon under these conditions is weak compared to the robust H 2 O 2 response. As a result, only a few members of the regulon are induced at or above our detection limits.…”
Section: Resultsmentioning
confidence: 55%
“…S5) (35). This suggests either that OxyR does not respond directly to sulfane sulfur in A. baumannii as previously observed in E. coli (44) or that the induction of the OxyR regulon under these conditions is weak compared to the robust H 2 O 2 response. As a result, only a few members of the regulon are induced at or above our detection limits.…”
Section: Resultsmentioning
confidence: 55%
“…Recently, it was shown that the signaling role of H 2 S is via sulfane sulfur, which is sensed by gene regulators that activate the genes involved in H 2 S oxidation in bacteria (51)(52)(53). OxyR also senses high levels of cellular sulfane sulfur to produce enzymes for its removal (54). Our evidence suggests that sulfane sulfur is likely involved in regulating photosynthetic genes ( Fig.…”
Section: Discussionmentioning
confidence: 64%
“…Previously, we discovered that deleting OxyR, the redox-sensitive transcriptional factor, in E. coli BL21 leads to a notable increase in its intracellular polysulfide level ( 11 ). On the basis of the conclusion of the report ( 10 ), we speculated that the protein persulfidation level should also be higher in E. coli BL21Δ oxyR than in E. coli BL21 wild type (wt).…”
Section: Resultsmentioning
confidence: 99%